Face transplantation surgical options and open problems in cadaveric models: A review article. Issue 3 (26th February 2013) - Baccarani, Alessio; Follmar, Keith E.; Erdmann, Detlev; Levin, L. Scott
Abstract: Being first conceptualized in 2005–2006, total face transplantation is now a clinical reconstructive option in the treatment of patients with acquired facial deformity. The authors propose a review on the status of total face transplantation based on their clinical experience in dealing with traditional microsurgical head and neck reconstructions and on the basis of their published pre‐clinical research investigating technical aspects of the facial allotransplantation procedure in cadaveric models. The authors first discuss the harvesting options and propose two facial flaps which address different reconstructive needs. Next, the concept of donor–recipient anatomical compatibility is introduced, and the possible outcome of the chimeric face is studied, following the insetting of a fasciocutaneous facial allograft. Finally, the authors address the major technical challenges associated with transplanting the most complex osteomyocutaneous allograft. Significant improvement has been made in the field of vascularized composite tissue allotransplantation over the last 5–6 years. The results of the 13 face transplants performed worldwide are encouraging both functionally and aesthetically, when compared with traditional reconstructive procedures. © 2013 Wiley Periodicals, Inc. Microsurgery, 2013.